Spontaneously Developed Bisphosphonate Related Osteonecrosis of the Jaws: Three Cases - Ates, Ufuk; Gulsahi, Ayse (The Journal of Dentists, 2014)
Aim: The aim of this case report is to present the clinical and radiologic diagnose of the spontaneously developed bisphosphonate-related osteonecrosis of the jaws in the edentulous patients. Background: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a common side effect of long term bisphosphonate therapy. It is characterized with the presence of exposed necrotic bone appearing in the jaws of patients treated bisphosphonates never irradiated in the head and neck area. BRONJ lesions may occur spontaneously or at the site of a dentoalveolar procedure. Clinically evident lesions are confirmed through radiographs showing poorly defined radiolucent- radiopaque lesions. At present, no predictable remedy is available for BRONJ. Case Description: Three edentulous male patients were referred to our clinic for non-healing defect in the posterior region of the mandible. Medical anamnesis revealed prostate carcinoma and the use of zoledronate (Zometa). Clinical examinations showed oval shaped defect or exposed necrotic bone. Digital panoramic radiographs revealed destructive radiolucent area. Biopsy was performed for the exclusion of the metastic disease and revealed inflammation consistent with osteomyelitis. Treatment protocol included systemic antibiotic therapy and conservative surgical treatment. Clinical Significance: BRONJ should be mentioned that presence of exposed necrotic bone or non-healing oral mucosa in patients with a history of bisphosphonate use without a history of dentoalveolar procedures.